Insight into the Stigma of Suicide Loss Survivors: Factor Analyses of Family Stereotypes, Prejudices, and Discriminations. Issue 1 (2nd January 2018) - Corrigan, Patrick W.; Sheehan, Lindsay; Al-Khouja, Maya A.; Lewy, Stanley; Major, Deborah R.; Mead, Jessica; Redmon, Megghun; Rubey, Charles T.; Weber, Stephanie
Abstract : Families of individuals who die by suicide report public stigma that threatens their well-being. This study used a community-based participatory (CBPR) approach to describe a factor structure for the family stigma of suicide. Candidate items (n = 82) from a previous qualitative study were presented in an online survey format. Members of the public (n = 232) indicated how much they thought items represented public views and behaviors towards family members who lost a loved one to suicide. Factor analyses revealed two factors for stereotypes (dysfunctional, blameworthy), one factor for prejudice (fear and distrust), and three factors for discrimination (exclusion, secrecy, and avoidance).